Association of baseline core volume and early midline shift in acute stroke patients with a large ischaemic core - Yi, Ting-yu; Wu, Yan-min; Lin, Ding-lai; Lang, Feng-long; Yang, Yu-yan; Pan, Zhi-nan; Zheng, Xiu-fen; Hong, Gan-ji; Wu, Mei-hua; Lin, Xiao-hui; Chen, Rong-cheng; Zeng, Lisan; et al. (Frontiers in Neurology, 2023)
Background Midline shift (MLS) is troublesome problem that may occur in patients with a large infarct core (LIC) and may be related to the baseline infarct core volume. The purpose of this study was to explore the relationship between baseline infarct core volume and early MLS presence. Materials and methods Patients with acute intracranial large artery occlusion and a pretreatment relative cerebral blood flow (rCBF) <30% volume ≥50 ml on CT perfusion (CTP) were included, clinical outcomes following endovascular treatment (EVT) were retrospectively analyzed. The primary endpoint was MLS within 48 h (early MLS presence). The association between baseline ICV and early MLS presence was evaluated with multivariable regression. Results Ultimately, 95 patients were included, and 29.5% (28/95) of the patients had early MLS. The number of patients with a baseline rCBF < 15% volume (median [interquartile range], 46 [32–60] vs. 29 [19–40]; P < 0.001) was significantly larger in the early severe MLS presence group. A baseline rCBF < 15% volume showed significantly better predictive accuracy for early MLS presence than an rCBF < 30% volume (area under the curve, 0.74 vs. 0.64, P = 0.0023). In addition, an rCBF < 15% volume ≥40 ml (odds ratio, 4.34 [95% CI, 1.571–11.996]) was associated with early MLS presence after adjustment for sex, age, baseline National Institutes of Health Stroke Scale score, onset-to-recanalization time. Conclusion In patients with an acute LIC following EVT, a pretreatment infarct core volume > 40 ml based on an rCBF < 15% showed good predictive value for early MLS occurrence.